Empowering EFL Writers: The Impact of Unlimited Time and Dictionary Use on Writing Accuracy - Sharafi, Mohammad; Ayatollahi, Mohammad Ali (International Journal of Essential Competencies in Education, 2025)
Intermediate EFL learners often struggle with producing accurate and coherent writing, particularly in settings constrained by limited time and restricted access to language resources. While prior research has separately examined the effects of dictionary use or time flexibility, this study explores the combined impact of both. Through a quasi-experimental design, 50 male intermediate EFL learners were divided into control and experimental groups. The experimental group received unlimited time and access to both digital and print dictionaries during writing tasks, while the control group followed traditional time-bound instruction without resource access. Results showed a significant improvement in the experimental group’s writing scores, which rose from a pre-test mean of 14.76 to a post-test mean of 16.72 (t(24) = -5.70, p < 0.001, Cohen’s d = 1.06). The control group’s post-test mean was 15.12, and between-group comparisons also revealed a statistically significant difference (t(48) = 3.121, p = 0.003, Cohen’s d = 0.88). Error analysis further supported the intervention’s effectiveness, with reductions exceeding 50% in key error categories such as verb tense (from 43 to 21), sentence structure (27 to 13), and spelling (28 to 12). These results affirm that integrating flexible time policies and dictionary access enhances learners’ ability to self-monitor, revise, and control their writing. The study advocates for instructional models that promote learner autonomy, highlighting the need for EFL curricula to support more adaptive, resource-enriched learning environments. This dual-intervention model offers a practical pathway to elevate writing proficiency and reduce persistent error patterns in EFL contexts.